The difference and similarity of the big 4 companies: facts of attractiveness - Sadibek, R.; Seidakbarova, A.; Baimukanova, L.; Ashimkhanov, I. (International School of Economics KAZGUU, Nur-Sultan, 2022)
The Big Four are the four largest companies providing independent audit and consulting services. As of 2017, there are 945,000 people employed by the Big Four around the world. It is considered that it is prestigious to work as a consultant, auditor or lawyer in EY, Deloitte, KPMG or PwC. These companies, unlike many domestic ones, with great enthusiasm invite students with no experience to start a career with them and offer paid and free internships. However, the reverse side is also known - overtime, lack of sleep, eternal stress and low wages. Most Kazguu students, as noted, tend to work in these companies. But not everyone understands where to go, where are the best conditions for work. It turned out that in Kazakhstan, the employees of the Big Four also divide these companies into prestige and levels of conditions for an employee in companies. For example, which one they consider prestigious in Kazakhstan or where conditions are better. Since last year, it has been very noticeable that many of the students, who are employed into Big4, have been transferred to other companies. The main goal of this project is to give students information so that they understand the difference between each company.
Keywords: Big Four, independent audit, consulting services